Efficient algorithm for discrimination of overlapping ultrasonic echoes - Fortineau, Julien P.; Vander Meulen, François; Fortineau, Jérôme; Feuillard, Guy (Ultrasonics, 2017)
•Overlapped ultrasonic echoes are identified using an iterative algorithm.•One echo is identified at each iteration.•The effectiveness and the robustness of the method are studied.•Measurement can be achieved in a wide range of situations.•Ultrasonic velocities and thicknesses are simultaneously determined. We propose a method to identify the different echoes of an overlapped ultrasonic signal. This method is based on an iterative algorithm that compares the experimental signal to a realistic dictionary of trial functions and allows identification of one overlapped echo at each iteration. Adding physical parameters to the dictionary such as sample attenuation and ultrasound beam diffraction allows the method to be applied to various materials and sample geometries. Measurements at 500kHz and 5MHz on a ABS material and a copper plate are reported. The effectiveness and the robustness of the method are studied as a function of time delay between the different echoes. We show that taking into account the experimental set-up and material properties in the development of the dictionary are critical to identifying a round-trip signal when overlapping occurs.